Pharmacokinetics of standard versus high-dose isoniazid for treatment of multidrug-resistant tuberculosis. (9th June 2022) - Gausi, Kamunkhwala; Chirehwa, Maxwell; Ignatius, Elisa H; Court, Richard; Sun, Xin; Moran, Laura; Hafner, Richard; Wiesner, Lubbe; Rosenkranz, Susan L; de Jager, Veronique; de Vries, Nihal; Harding, Joseph; et al.
Abstract: Background: The WHO-endorsed shorter-course regimen for MDR-TB includes high-dose isoniazid. The pharmacokinetics of high-dose isoniazid within MDR-TB regimens has not been well described. Objectives: To characterize isoniazid pharmacokinetics at 5–15 mg/kg as monotherapy or as part of the MDR-TB treatment regimen. Methods: We used non-linear mixed-effects modelling to evaluate the combined data from INHindsight, a 7 day early bactericidal activity study with isoniazid monotherapy, and PODRtb, an observational study of patients on MDR-TB treatment including terizidone, pyrazinamide, moxifloxacin, kanamycin, ethionamide and/or isoniazid. Results: A total of 58 and 103 participants from the INHindsight and PODRtb studies, respectively, were included in the analysis. A two-compartment model with hepatic elimination best described the data. N -acetyltransferase 2 ( NAT2 ) genotype caused multi-modal clearance, and saturable first-pass was observed beyond 10 mg/kg dosing. Saturable isoniazid kinetics predicted an increased exposure of approximately 50% beyond linearity at 20 mg/kg dosing. Participants treated with the MDR-TB regimen had a 65.6% lower AUC compared with participants on monotherapy. Ethionamide co-administration was associated with a 29% increase in isoniazid AUC. Conclusions: Markedly lower isoniazid exposures were observed in participants on combination MDR-TB treatment compared with monotherapy. Isoniazid displays saturable kinetics at doses >10 mg/kg. The safety implications of these phenomena remain unclear.